PREVALENCE OF NON-ALCOHOLIC FATTY LIVER DISEASE AMONG OBESE PREGNANT WOMEN - I. O. Makarov; E. I. Borovkov; R. D. Kazakov (Акушерство, гинекология и репродукция)
In current work examination of 150 obese women with normal body weight was conducted. Peculiarities of pregnancy period and delivery are described. The structure of developed complications, as well as prevalence of nonalcoholic fatty liver disease among them are presented. It is revealed, that in 52% of pregnant women with obesity ultrasound signs of fatty degeneration of the liver are present. However, typical changes in blood biochemical analysis are detected only in 12% of patients. Thus, management of pregnancy in obese women should includeliver ultrasound examination. And in case of evaluation of fatty liver distrophyhepatoprotectors and membrane stabilizers with low fatty diet should be indicated.